Síntese e caracterização de complexos polipiridínicos de Ru(II) com diferentes ligantes carboxilatos e avaliação da reatividade frente ao oxigênio molecular - Sousa, Sinval Fernandes de (2019)
In this work, the influence carboxylate ligands on the spectral properties of bis-heteroleptic Ru(II) complexes and their reactivity with molecular oxygen was evaluated. For that, the complexes [Ru(bpy)2(pirc)]+, [Ru(bpy)2(acpy)]+ and [Ru(bpy)2(qui)]+, in which bpy = 2,2'-bipyridine, pirc = 2-pyridilcarboxylate, acpy = 2-pyridilacetate and qui = 2-quinolilcarboxylate were synthesized. The absorption spectra of the complexes were obtained in solution and featuring wide bands in the visible region attributed to MLCTdRu->π*bpy transitions, with some influence from the carboxylate ligands, as verified by TD-DFT calculations. The cyclic voltamograms of the [Ru(bpy)2(pirc)]+ and [Ru(bpy)2(qui)]+ complexes in acetonitrile are characterized by reversible processes attributed to the Ru(II/III) pair with E1/2 equal to +0.88 V and +0.90 V vs Ag/AgCl, respectively. Differently, the ciclic voltamogram of the [Ru(bpy)2(acpy)]+ complex in CH2Cl2 presented two peaks with E1/2 equal to +0.55 V and +0.92 V vs Ag/AgCl, attributed to the Ru(II/III) and Ru(III/IV) pairs, respectively and a third anodic peak at 1.18 V vs Ag/AgCl associated with the oxidation of the acpy ligand. The complex [Ru(bpy)2(acpy)]PF6 when exposed to the ambient atmosphere or in aerated solution reacts with O2 yielding the [Ru(bpy)2(acpyoxy)]PF6 complex, whose structure was confirmed by X-ray crystallography. The spectral and electrochemical properties of this complex and the reactivity of the [Ru(bpy)2(acpy)]PF6 complex with O2 were studied aiming a better understanding of the oxidation mechanism of the acpy ligand coordinated to the Ru (II). Through kinetic studies of the oxidation reaction by UV-Vis and 1H NMR, thermodynamic data obtained by DFT and identification of intermediates by mass spectrometry, it was possible to conclude that the addition of an oxygen atom to the α carbon in the acpy ligand occurs through three steps: nucleophilic attack of the molecular O2 at the Ru(II) center for formation of Ru(IV)=O; activation of the C-H bond and formation of a relatively stable -hydroxy-carboxylate intermediate, the latter being the kinetic limiting step. A new attack by the molecular O2 at the Ru(II) center in the intermediate followed by an internal rearrangement leads to the second oxidation of the Cα and yields the final product with release of a water molecule.